Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Ulm, Sean; McNiven, Ian J.; Summerhayes, Glenn R.; Wu, Pei-hua; Bunbury, Magdalena M.E.; Petchey, Fiona; Hua, Quan; Skelly, Robert; Lambrides, Ariana B.J.; Rowe, Cassandra; Lowe, Kelsey M.; Reepmeyer, Christian H.; et al. (Quaternary Science Reviews, 2024)
Aboriginal manufacture and use of pottery was unknown in Australia prior to European settlement, despite well-known ceramic-making traditions in southern Papua New Guinea, eastern Indonesia, and the western Pacific. The absence of ancient pottery manufacture in mainland Australia has long puzzled researchers given other documented deep time Aboriginal exchange networks across the continent and the close proximity of pottery-bearing Lapita and post-Lapita maritime communities in the western Pacific with ocean-going watercraft and sophisticated navigation abilities. We report the oldest securely dated ceramics found in Australia from archaeological excavations on Jiigurru (Lizard Island Group) on the Great Barrier Reef, northeast Australia. Comprehensive radiocarbon dating and Bayesian modelling constrains ceramic deposition to between 2950–2545 cal BP and 1970–1815 cal BP. This timing overlaps with late Lapita and post-Lapita ceramic traditions of southern Papua New Guinea. Geological characterisation of the sherds strongly suggests local manufacture as the vessels belong to three temper and clay groups locally sourced to northeast Australia, and most likely to Jiigurru. The oldest occupation layers date to 6510–5790 cal BP, making Jiigurru the earliest offshore island occupied on the northern Great Barrier Reef. The results demonstrate that northeast Australian First Nations communities had sophisticated canoe voyaging technology and open-sea navigational skills and were intimately engaged in ancient maritime networks, connecting them with peoples, knowledges, and technologies across the Coral Sea region.